Becoming a Nurse at Sporting Events: a Qualitative Exploration of Professional Practices and Challenges - Ramadhan, Muhammad Putra; Rahamtika, Qory Tifani; Fidyasanti, Neni; Evi, Nurul; Afiani, Nurma; Fai’zaturrizqiyyah, Fai’zaturrizqiyyah (Jurnal Locus Penelitian dan Pengabdian, 2025)
Background: The advancement of modern sports demands a comprehensive, rapid, and responsive healthcare system, wherein nurses—as integral members of multidisciplinary medical teams—play a crucial role in safeguarding athlete safety and performance. This study aimed to explore nurses’ experiences, roles, challenges, and expectations as part of medical teams during sporting events.  Methods: A qualitative study employing a phenomenological approach was conducted to gain in-depth insights into the experiences of eight nurses who had served on sports medical teams in Malang, Indonesia. Data were collected through in-depth interviews and analyzed thematically. Results: Five main themes emerged: (1) background and motivation, (2) roles and responsibilities, (3) interprofessional collaboration, (4) practical challenges in the field, and (5) expectations and recommendations. Nurses participated due to personal and professional motivations, fulfilling dynamic roles ranging from first aid provision to health education. However, they encountered limitations such as inadequate equipment, heavy workloads, and unclear authority boundaries. They also expressed desires for specialized training and greater professional recognition. Conclusion: Nurses are essential pillars within sports medical teams, yet systemic support is needed to strengthen their roles and professional standing.